1992
DOI: 10.1080/00050069208257573
|View full text |Cite
|
Sign up to set email alerts
|

The long-term adjustment of 60 persons with spinal cord injury

Abstract: This study utilised the constructs employed in Schulz and Decker's (1985) study of the long-term adjustment of 100 middle-aged and elderly persons who had lived with spinal cord injury (SCI) for an average of 20 years. In a major departure from that study, a relatively younger group of persons with traumatic SCI was interviewed an average of 11 years after onset of disability. They answered questions conceming perceived control, health status, social support, satisfaction with social contact, and, in addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…This supports previous findings 1,17,35,60,61,63,[69][70][71][72] and also provides support for occupational therapy's premise: that occupation is a source of meaning, purpose, choice and control and that engagement in personally meaningful occupations contributes to the experience of a life worth living. 48 However, occupational therapy theory has demonstrated a clear difficulty with differentiating between the concepts 'purposeful', and 'meaningful', sometimes using the terms interchangeably and tending to extol the notion of meaningful occupation while focusing specifically on purposeful, goal-oriented, socially sanctioned use of time and energy in 'doing', congruent with the values and ideology of Western culture.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This supports previous findings 1,17,35,60,61,63,[69][70][71][72] and also provides support for occupational therapy's premise: that occupation is a source of meaning, purpose, choice and control and that engagement in personally meaningful occupations contributes to the experience of a life worth living. 48 However, occupational therapy theory has demonstrated a clear difficulty with differentiating between the concepts 'purposeful', and 'meaningful', sometimes using the terms interchangeably and tending to extol the notion of meaningful occupation while focusing specifically on purposeful, goal-oriented, socially sanctioned use of time and energy in 'doing', congruent with the values and ideology of Western culture.…”
Section: Discussionsupporting
confidence: 89%
“…3,4,[58][59][60][61]70,71,[86][87][88][89][90][91][92][93] In this study, it was impossible to differentiate the notion of social activities from the dual concepts of 'relationships' and 'doing'. When the participants spoke of their relationships with families and friends it was frequently in the context of activities: travelling, going out to restaurants, bars, theatres, concerts, etc.…”
Section: Discussionmentioning
confidence: 99%
“…12 When Crisp replicated Schulz and Decker's study methods with a di erent sample of persons with SCI, his results did not corroborate those of the earlier study. 10,13 Contrary to Schulz and Decker, neither age nor age at injury was signi®cantly related to any of the adjustment measures used. 13 It is not clear whether the lesser age (by a mean of 20 years) and lesser time since injury (by 10 years) of Crisp's sample may have contributed to these negative ®ndings.…”
Section: Studies Of Aging and Scimentioning
confidence: 58%
“…36 In contrast, a substantial body of research has found no correlation between QOL/life satisfaction and level of SCI: the degree of impairment or extent of physical independence. 9,15,20,48,49,52,60, Meta-analyses of research into QOL following SCI reported by Evans et al 75 and Dijkers 36 have demonstrated the wide variety of research designs and instruments, modes of analysis and sample characteristics that make comparisons and overall conclusions problematic. These difficulties were further explored in a review published by Hallin et al, 107 who identified the need for 'carefully constructed condition-specific instruments that can capture dimensions of specific interest for the SCI population' (p 520).…”
Section: Qol Following Sci: Quantitative Findingsmentioning
confidence: 99%
“…The Life Satisfaction Index-A (LSI) 46 is considered to be most suitable for use with people over 65 years of age 47 yet has been used in several studies of people with SCI. [48][49][50] This must be considered in light of evidence that the mean age of SCI in the USA is 32 years and that 55% of injuries occur among people aged 16-30 years. 51 Further, while the majority of seniors are women, about 82% of those with spinal cord injuries are men.…”
Section: Assessing Qol Following Scimentioning
confidence: 99%